2023
DOI: 10.3390/diagnostics13030522
|View full text |Cite
|
Sign up to set email alerts
|

Post-COVID Endocrine Disorders: Putative Role of Molecular Mimicry and Some Pathomorphological Correlates

Abstract: In order to identify corresponding amino acid sequences (pentapeptides) between the SPs, MPs and NPs of human coronaviruses and human autoantigens targeted in autoimmune endocrinopathies, and for a comparative analysis of the various coronaviruses proteome and the proteome of human, the original computer program was used. Quantitatively, SP, MP and NP of the human coronaviruses were found to share totally 117 minimal immune pentapeptide epitopes: 79 in SP, 14 in MP and 24 in NP, – with 18 autoantigens expresse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…Several pathways were suggested to operate in the SARS-CoV-2-AD cross-talks [1,11,12]. However, the most accepted and reported mechanism is molecular mimicry between the viral epitopes and human antigens [9,40,41,53,111]. Molecular mimicry is defined as the process where sequence similarities between foreign and self-peptides are sufficient to result in the cross-activation of B or autoreactive T cells, induced by pathogen-derived peptides [39,112].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several pathways were suggested to operate in the SARS-CoV-2-AD cross-talks [1,11,12]. However, the most accepted and reported mechanism is molecular mimicry between the viral epitopes and human antigens [9,40,41,53,111]. Molecular mimicry is defined as the process where sequence similarities between foreign and self-peptides are sufficient to result in the cross-activation of B or autoreactive T cells, induced by pathogen-derived peptides [39,112].…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms drive autoimmunity [1]: molecular mimicry [19,[39][40][41], epitope spreading [42,43], bystander activation [44,45] violation of biological barriers in immune-privileged organs [46], polyclonal activation of lymphocytes as a result of the action of superantigens [47], and finally, immune cross-reactivity between non-self-and self-antigens [48][49][50][51][52]. Several of those modes of action were even suggested to drive SARS-CoV-2-associated autoimmunity [1,11,12,40,[47][48][49][50]53]. A major under-studied aspect of the SARS-CoV-2-induced ADs is the molecular mimicry between the virus and the enteric epitopes.…”
Section: Introductionmentioning
confidence: 99%
“…In immunology, "molecular mimicry" has been used for identifying sequence similarities between pathogens and the host regardless of evolutionary cheating, suggesting that such similarities may induce autoantibodies leading to autoimmune diseases. Many studies have reported that COVID-19 is associated with autoimmune responses [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64]. Indeed, many spike epitopes of antibodies from COVID-19 patients have been identified [65][66][67][68][69][70][71][72][73][74][75][76], but whether these anti-spike antibodies cross-react with human proteins is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…PCC is defined as the continuation or development of new symptoms after 3 months from infection, lasting for a minimum period of another 2 months [9]. Its manifestations derive from multiple mechanisms that the virus has the potential of inflicting [10]; SARS-CoV-2 interacts with the host microbiome/virome, paving the way for the reactivation of pathogens such as herpesviruses or fungi under the conditions of immune dysregulation [11][12][13][14][15]; it damages the vessel endothelium and provokes clotting issues [16,17]; it alters the brainstem and vagus nerve signaling because of its neuroinvasive capabilities [18][19][20]; finally, it provokes autoimmunity due to immune cells' overactivity and molecular mimicry between pathogens and the host proteins [21,22].…”
Section: Introductionmentioning
confidence: 99%